PERANCANGAN DAN PENGELOLAAN WEB STT YESTOYA SEBAGAI MEDIA KOMUNIKASI PELAYANAN MAHASISWA - Inri Inggrit Indrayani; Lady Joanne Tjahyana (Institute of Research and Community Outreach - Petra Christian University, 2013)
This community service is conducted to do designing and maintaining STT Yestoya web as communication media for students services. According to the objective above this community service has involved and empowered the students of STT Yestoya as the actors in utilization of the web of the institution. The impact of this project is expected to increase the student ability in managing web in order to develop their congregations in the utilization of the internet. The project mechanism is done by giving coaches and practices that organized in three phases. The topics are photography for media, web development and writing for the web. The results of the community service are to raise writing skill, take the best angle of photoes and maintain web by the teamwork.